Examination of Hausa Terms and Concepts Used over Electronic Media in the Western Hausa Dialect Area - Usman Ahmadu, Mohammed (Glottodidactica, 2005)
The study is set up to examine Hausa terms and concepts used over the Nigeria electronic media. Specifically the study analyses the use of Hausa in the eastern Hausa dialect area where we sample Katsina and Sokoto States in Nigeria. Through various instruments of research, the study comes up with various performances of the Hausa Broadcasters in terms of lOVs, IOAs, IOCs, and IOls. The study identifies that there are various degrees of variations among Hausa Broadcasters in the use of terms and concepts in the electronic media in the western Hausa dialect area. These variations are observed at different levels i.e. among Hausa Broadcasters in the same electronic media within the same dialect area and across electronic media. These variations occasion various degrees of performances among Hausa Broadcasters in terms of IOAs. The study further identifies various degrees of performances in terms of IOCs, which result in various degrees of performances in terms of IOIs.